ANALYSIS OF SATISFACTION AND LOYALTY DEGREE OF CONSUMERS TOWARD HEALTHY CATFISH BOOSTER PURCHASING - Febrika Nurmalasari; Harsuko Riniwati (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Farm Fish Booster Centre is one of the business actor in Indonesia whom focus on cultivation  and catfish manufacture that named as healthy catfish booster. The purpose of this study is to analyze the degree of satisfaction and consumer loyalty toward healthy catfish booster purchasing. Research method that used is descriptive with quantitative approach. The number of samples that usedare 100 respondents who determined by slovin formula. The method of collecting data by questionnaire, interview and documentation. Satisfaction variables indicators consist of the performance and interests: brand, price, taste, clean from foreign objects, ease of finding the products, packaging design, the availability of halal guarantee, the availability of the expired date, shelf life of the product and sale locations. Loyalty variables indicators consist of price, habit, satisfaction, likes and loyal to the brand. Methods of data analysis using descriptive analysis, importance performace analysis (IPA) and customer satisfaction index (CSI). The results of this study showed that customer satisfaction towards every attribute the highest one is attribute flavor (91,04%) while lowest attribute is the availability of expiration date (33.05%). Consumer overall stated are quite satisfied with the value of CSI (64.4%) towards healthy catfish booster. The degree of consumer loyalty are weak classified, 73% of consumers classified as a switcher buyer. Keywords: satisfaction, consumer, loyalty, lele boster